A Five Year financial plan for the Electric Group (Phil.) Corporation - Socito, Leira Mae M. et. al. 4 0 16; 5 (2018)
EXECUTIVE SUMMARY: This study is design to create a financial plan of The Electric Group (Phil.) Corporation. The financial problem is mainly focused on having low profitability level of entity. The analysts used a five-year audited financial statements of the entity from 2012-2016 to make a financial analysis of the entity's problem. After carefully studying both internal and external environment of the entity, the financial ratios and historical data of the entity through their financial statements, the analysts come up to have four alternative courses of action. These are Switching of Supplier with the same brand of different locale (China),. Purchase products from local exclusive distributor by buying only marketable products. Diversification of Brands and Obtaining lower cost of supplies from China and retain lower cost of supplies from Malaysia. Among these four courses of action, the analysts decided that Obtaining lower cost of supplies from China and retain lower cost of supplies from Malaysia is the best suited course of action to implement based on the financial problem they have in the entity. With the use of forecasted financial statements of the entity, the analysts projected the financial statements of the entity after employing the selected course of action. The course of action by the analysts was able to increase Net Profit by 150% to 250% by the end of the year of implementation, decrease the entity's Cost of Sales by 12% during the implementation and improve Liquidity Position during the 5-year plan.
Financial Plan: (BSBA major in Finance and Treasury Management) - Pamantasan ng Lungsod ng Maynila, 2018.
Keywords: 2 -- 0; 6; 20; 20; 2